2013
DOI: 10.1186/1757-7241-21-24
|View full text |Cite
|
Sign up to set email alerts
|

Blood alcohol concentration and self-reported alcohol ingestion in acute poisoned patients who visited an emergency department

Abstract: BackgroundMany acute poisoned patients have co-ingested alcohol in the emergency department (ED). This study aimed to estimate the blood alcohol concentration (BAC) of acute poisoned patients who visited an ED by age and gender distribution and to determine whether it is possible to obtain self-reports of alcohol ingestion among poisoned patients.MethodA retrospective medical chart review was conducted for all patients who visited the ED with acute poisoning between January 2004 and February 2008. Data regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…It was also observed that the average BAC in males was higher. These findings are in keeping with those of Woo et al [19].…”
Section: Discussionsupporting
confidence: 93%
“…It was also observed that the average BAC in males was higher. These findings are in keeping with those of Woo et al [19].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the early detection of drinking problems and early interventions for suicide attempters who visit the emergency department (ED) are important to reduce the risk of suicide reattempt. However, among suicide attempters, obtaining the exact related history is often difficult because of mental confusion or physical problems, and they tend to under-report or hide their problems [12, 13]. Difficulties in detecting alcohol problems among suicide attempters in emergency situations include limited time, manpower, and treatment based only on acute symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…First, we identified the alcohol-related group based on the self-reported use of alcohol. However, self-reported data has proven to be valid information in several studies including in Korea [ 18 , 19 ]. In addition, self-reported drinking could be more inclusive, because blood alcohol concentration could be affected by the amount of time passed between the injury and arrival at the ED [ 20 ].…”
Section: Discussionmentioning
confidence: 99%